Fabrication of Sustained-release CA-PU Coaxial Electrospun Fiber Membranes for Plant Grafting Application. (1st August 2017) - Guo, Zhongfu; Tang, Guosheng; Zhou, Yonghong; Shuwu, Liu; Hou, Haoqing; Chen, Zhenyu; Chen, Jinhui; Hu, Chunhong; Wang, Fei; De Smedt, Stefaan C.; Xiong, Ranhua; Huang, Chaobo
Graphical abstract: Highly elastic 6-Benzylaminopurine loaded CA-PU fiber membranes are prepared by electrospun (left) and subsequently cut into 2 cm wide bands (middle). The membranes are applied respectively to promote plant wound healing (top right) and improve graft survival (lower right). Highlights: PU (core)/CA (shell) coaxial fibers were obtained by co-electrospun. CA-PU coaxial electrospun fiber possess good mechanical properties. 6-BA loaded core-shell fibers can increase survival rate of the graft. Abstract: Plant grafting is a well-known activity in orchards, greenhouses and vineyards gardens. However, low survival rate still limits the promotion of grafting and breeding of improved varieties. We report on polymeric fibers, obtained through coaxial electrospun, as carriers for the sustained release of drugs to heal wounds in plants. The CA-PU co-electrospun fibers show a rather uniform diameter, a smooth and hydrophilic surface. As long as 10 days of sustained drugs release meets with the physiological requirement of plant grafting. The callus toxicity test shows that the CA-PU fibers are not toxic for plant cells. We show that loading the core of CA-PU fibers with 6-Benzylaminopurine (6-BA), a first-generation synthetic cytokinin that elicits plant growth and development, results in fibers that can efficiently promote the healing of plant wounds, thereby significantly improving the grafting survival rate.